THE INFLUENCE OF SIA QUALITY, INCENTIVES, AND LEVEL OF EDUCATION ON THE PERFORMANCE OF EMPLOYEES OF PERUMDA WATER TIRTA MANGUTAMA BADUNG - Michael Harris Frananta; Big Juliarsa (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
The sustainability and success of an organization can be seen from the performance of its employees. This research aims to evaluate the effect of implementing the Accounting Information System (AIS) on employee performance at PERUMDA Air Minum Tirta Mangutama Badung Regency. Analyze the effectiveness of providing incentives in increasing employee motivation and performance. Assess the role of employee education levels in improving their performance and contribution to the company's operational success.This research was conducted at PERUMDA Air Minum Tirta Mangutama, Badung Regency, different from previous research which was located at the Savings and Loans Cooperative, Gianyar Regency. The sample in this research was 94 employees using a purposive sampling technique in the sample determination method. The data analysis technique used in this research is multiple linear regression analysis. The research results show that the quality of SIA, provision of incentives, and level of education have a significant positive influence on employee performance at PERUMDA Air Minum Tirta Mangutama Badung Regency.